2013
DOI: 10.7314/apjcp.2013.14.11.6557
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase Assay to Screen Tumour-specific Promoters in Lung Cancer

Abstract: Objective: Specific promoters could improve efficiency and ensure the safety of gene therapy. The aim of our study was to screen examples for lung cancer. Methods: The firefly luciferase gene was used as a reporter, and promoters based on serum markers of lung cancer were cloned. The activity and specificity of seven promoters, comprising CEACAM5 (carcinoembryonic antigen, CEA), GRP (Gastrin-Releasing Peptide), KRT19 (cytokeratin 19, KRT), SFTPB (surfactant protein B, SP-B), SERPINB3 (Squamous Cell Carcinoma A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, earlier studies have revealed an IL-4/STAT-6/Tfec/IL-4Rα positive feedback regulatory loop, in which Tfec transcribes IL-4Rα expression to promote M2 programming in macrophages, which was implicated in asthma pathogenesis ( 57 ). In addition, several genes were involved in lung cancer and other lung diseases, such as Ceacam1 ( 58 , 59 ), Ereg ( 60 , 61 ) , Selp ( 62 , 63 ), and Pik3r5 ( 64 , 65 ). The most conspicuous genes among downregulated ones are members of the keratins (KRTs) and keratin-associated proteins (KRTAPs), including Krt34 , Krtap3-1 , and Krtap7-1 , which are important for epidermal development and hair follicle morphogenesis ( 66 , 67 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, earlier studies have revealed an IL-4/STAT-6/Tfec/IL-4Rα positive feedback regulatory loop, in which Tfec transcribes IL-4Rα expression to promote M2 programming in macrophages, which was implicated in asthma pathogenesis ( 57 ). In addition, several genes were involved in lung cancer and other lung diseases, such as Ceacam1 ( 58 , 59 ), Ereg ( 60 , 61 ) , Selp ( 62 , 63 ), and Pik3r5 ( 64 , 65 ). The most conspicuous genes among downregulated ones are members of the keratins (KRTs) and keratin-associated proteins (KRTAPs), including Krt34 , Krtap3-1 , and Krtap7-1 , which are important for epidermal development and hair follicle morphogenesis ( 66 , 67 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…DKK1 has been reported to be a biomarker in lung cancer, with high levels of specificity and expression ( 4 ). However, our previous study demonstrated low DKK1 promoter activity in lung cancer cells ( 6 ). In the present study, 12 TREs were predicted using DHS and histone modification analysis of the lung cancer-specific DKK1 locus in A549 cells using the UCSC genome browser.…”
Section: Discussionmentioning
confidence: 85%
“…As a control, the SV40 enhancer/promoter fragment was excised from pRL-TK and inserted in forward and reverse orientations into the pGL3-basic plasmid at the Xho I and Bgl II sites to produce pGL3-SV40. Genomic DNA extraction, polymerase chain reaction (PCR) amplification and concentration quantification were performed as previously described ( 6 ). All primer sequences and cloning sites are listed in Table I .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations